Strategi Guru Pendidikan Agama Islam Dalam Membentuk Kepribadian Remaja di SMA Negeri 1 Sragen - Armadany, Cintya Rachma; Dartim (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teachers in shaping adolescent personality at SMA Negeri 1 Sragen. The research employed a qualitative approach with a descriptive case study design. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using an interactive data analysis model. The findings indicate that personality development strategies were carried out in a planned, systematic, and collaborative manner through five main approaches: role modeling, religious habituation, integration of values into classroom instruction, personal mentoring, and collaboration among teachers. Role modeling emerged as the most dominant strategy, as students tend to imitate teachers’ behavior in daily interactions. Religious programs such as congregational prayer, Qur’anic recitation, Islamic student organization activities, and Friday religious programs function as instruments for internalizing religious and social values. These findings affirm that adolescent personality development requires an integrated strategy embedded within school culture and supported by a conducive educational environment.